Nasalance scores in Spanish-speaking children aged 3 to 5 years according to gender, age, and vowel load - Peris-Hernández, Cristina; Rosell-Clari, Vicent; Kummer, Ann W. (Revista de Investigación en Logopedia, 2024)
Nasometry is a non-invasive, easy-to-use technique that provides objective data regarding the amount of acoustic energy in the oral and nasal cavities during speech. The goal of this study is to create a Spanish passage and determine normative nasalance values for typical Spanish-speaking children, 3 to 5 years of age, that allows us to compare the values in children of the same age who present hypernasality and velopharyngeal dysfunction. Second, to determine if there are significant differences in nasalance scores based on age or gender. Third, to test the impact of vowel load on nasalance scores. Data were collected from 130 children with no known speech, language, or hearing disorder. Participants were organized into three groups according to age. A nasometric assessment protocol for Spanish was developed based on an adaptation of the MacKay-Kummer Simplified Nasometric Assessment Procedures-Revised (SNAP-R; 2005). All participants were required to repeat the speech stimuli. Data were collected using the icSpeech nasometer and were recorded on EXCEL 365 sheets for further analysis. Normative data is now available for a Spanish version of the SNAP-R Test. No significant differences were found between the genders, but significant differences were found based on age. It was also found that a load of high and anterior vowels, especially the phoneme /i/, increased nasalance scores. This protocol created passages in Spanish that mimic the passages of the SNAP-R Test in English. These Spanish passages were normed for Spanish-speaking children. This study confirms that high vowels result in higher nasalance values and therefore, the vowel composition of a specific passage determines the nasalance score, not the language of the passage.